Spatial analysis of identifying the association between risk factors and tuberculosis cases: a review - Mohidem, Nur Adibah; Osman, Malina; Hashim, Zailina; Muharam, Farrah Melissa; Mohd Elias, Saliza; Ma'pol, Aminuddin (Universiti Pendidikan Sultan Idris, 2024)
This article address one of critical analysis which is needed in epidemiology. Tuberculosis transmission frequently manifests in a variety of spatial configurations. Nonetheless, the observed spatial clustering of tuberculosis may signify either ongoing transmission or the co-location of pertinent risk factors. This investigation seeks to critically assess the spatial analyses employed for the surveillance of trends regarding the associations between risk factors and tuberculosis cases through the application of spatial epidemiology principles. Prior investigations incorporating spatial analysis of tuberculosis cases, which encompass methodologies such as kriging, spatial autocorrelation, kernel density estimation, hotspot analysis, and regression analysis, are systematically reviewed. The selection of the analytical method was predicated upon the objectives of each respective study. In various contexts, an array of distinct spatial analysis techniques was implemented, with all studies revealing considerable heterogeneity in the spatial distribution of tuberculosis. Future inquiries remain imperative. An integrative approach combining genotypic, molecular, and geospatial methodologies for the examination of epidemiologically interconnected cases could enhance tuberculosis control efforts and yield substantial contributions to the existing body of knowledge.